1971
DOI: 10.1002/app.1971.070150402
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of alternating polyamideurethans by reacting diisocyanates with N,N′‐di‐(6‐hydroxy‐caproyl)alkylenediamines and N‐hydroxy‐alkyl‐6‐hydroxycaproamide

Abstract: synopsisPolyamideurethans of structures I and I1 were prepared by reacting N,N'-di-(6-hy-droxycaproy1)alkylenediamines and N-hydroxyalkyl-6hydroxycaproamide with hexa-met>hylene diisocyanate and 4,4'-diphenylmethane diisocyanate : I1where R1 is either a dimethylene or hexamethylene radical, and Rz is a hexamethylene or 4,4'-diphenylmethane radical. Polymers I and I1 were of a high degree of polymerization and crystallinity, had high enough melting points for practical use, and gave colorless tough flms both by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 8 publications
4
20
0
Order By: Relevance
“…Previous research showed that the incorporation of symmetrical bisamide-diol monomers into the backbone of biodegradable polyesters enhanced the thermal and mechanical properties of these materials [21][22][23][24][25][26][27][28][29][30][31][32][33]. These poly(ester amide)s have a micro-phase separated structure with an amide-rich hard phase and an esterrich flexible soft phase.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showed that the incorporation of symmetrical bisamide-diol monomers into the backbone of biodegradable polyesters enhanced the thermal and mechanical properties of these materials [21][22][23][24][25][26][27][28][29][30][31][32][33]. These poly(ester amide)s have a micro-phase separated structure with an amide-rich hard phase and an esterrich flexible soft phase.…”
Section: Introductionmentioning
confidence: 99%
“…Bisamide-diols are conveniently synthesized through ring-opening of lactones by a,u-diamines [4,5,21,[24][25][26][27]. Polycondensation of such bisamide-diols with dimethyl adipate and aliphatic diols has been intensively investigated [5,7,21,23,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting that these orders are consistent with the orders of the melting points of the amide diols, dimethyl carboxylates, and dicarboxyloyl chlorides, similar to the case of polyamide urethanes in our previous paper. 22 To evaluate the melting points, Korshak-Phrynze's c o n s t a n t~~~?~* on melting points were calculated and are tabulated in Table VII …”
Section: Melting Pointmentioning
confidence: 99%
“…The smaller T d of CPPD polymers may be due to the more acidic N-hydrogen which causes the thermal decomposition of the ester linkage since the ester linkage is weaker to acid than the amide linkage. 22 The difference of T i and T , is of the following order:…”
Section: Thermal Stabilitymentioning
confidence: 99%